Gestão da qualidade aplicada à sistemas de segurança do alimento: uma análise da aplicação do Controle Estatístico do Processo para a melhoria do Processo de Produção de Carcaças de Frango numa indústria avícola - Cima, Elizabeth Giron (2006)
This paper objective was to verify Statistical Process Control (SPC) through the PDCA cycle, in a boiler process plant located in the West region of Paraná, Brazil. Chicken carcass was selected as raw material. Water temperature in the pre-cooling system, water temperature in the cooling system, and carcass temperature at the closing stage of the system were the monitored variable that made up raw material. Data were collected between January 2005 and May 2006. Daily samplings were taken where daily and weekly sub-groups were considered. To execute SPC, we applied X and S control graphs for weely analysis; individual X AM graphs, just in case it would be a daily study; EWMA, tubular form CUSUM and V Mask CUSUM pondered control graphs for weekly analysis, as well as performance and capacity indicators to study the production process. It was concluded through the CEP study to continue perform analysis of possible variations that occur in the production process and interpret these variations to identify nonconformities. Through the cause and effect graph, specific variation of the PDCA cycle was suggested as a way to prevent and eliminate these variations of the process. Actions Plans were elaborated through the QC STORY (problem solving method) method for continuous improvement of the carcass cooling process in the plant. Finally, based on the SIX SIGMA method, the process quality level was evaluated, where it became evident that the broiler carcass cooling process is no being able to produce broiler carcass with zero degree defects